2015
DOI: 10.1097/brs.0000000000000982
|View full text |Cite
|
Sign up to set email alerts
|

Low Back Pain

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Our research found that the four types of endplate defects differed in segment distribution, configuration features, and strength of association with the size of MCs. We found that LBP can be accelerated by the increasing prevalence of endplate defects, MCs, and DD, which was in accordance with previous studies [24, 27, 28]. Moreover, we were surprised to find that endplate defect group 1 (focal) was associated with the highest degree of disc degeneration (DD4).…”
Section: Discussionsupporting
confidence: 91%
“…Our research found that the four types of endplate defects differed in segment distribution, configuration features, and strength of association with the size of MCs. We found that LBP can be accelerated by the increasing prevalence of endplate defects, MCs, and DD, which was in accordance with previous studies [24, 27, 28]. Moreover, we were surprised to find that endplate defect group 1 (focal) was associated with the highest degree of disc degeneration (DD4).…”
Section: Discussionsupporting
confidence: 91%
“…This is particularly interesting considering most of the movement in the sagittal plane is contributed by the lumbar spine as compared to the dominance of thoracic spine motion for the axial and coronal planes [11, 34]. Reason for this lack of sagittal significance can be two-fold.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper we focus on subject-specific finite element (FE) analysis of articular joint contact mechanics. Both generic and subject-specific models of articular contact have been developed and validated to gain insight into load transfer, cartilage mechanics and the etiology of osteoarthritis in the knee (Khoshgoftar et al, 2015; Luczkiewicz et al, 2015), hip (Harris et al, 2012; Henak et al, 2014) ankle (Anderson et al, 2007; Kern and Anderson, 2015) and spine (Dreischarf et al, 2014; Von Forell et al, 2015), among other joints. Despite the progress that has been made in modeling subject-specific joint contact mechanics, many challenges still remain.…”
Section: Introductionmentioning
confidence: 99%